Radiation shielding and gamma ray attenuation properties of some polymers - Bhosale Rameshwar R.; More Chaitali V.; Gaikwad Dhammajyot K.; Pawar Pravina P.; Rode Madhav N. (Nuclear Technology and Radiation Protection, 2017)
In the present work we investigated the gamma radiation parameters as mass attenuation coefficients μ/ρ, the total atomic scattering cross-sections σν, the electronic scattering cross-sections se, the effective atomic numbers Zeff, and the effective electron densities Neff for some polymers such as polyoxymethylene (CH2O), poly acrylonitrile (C3H3N), natural rubber (C5H8), poly ethyl acrylate (C5H8O2), polyphenyl methacrylate (C10H10O2), and polyethylene tetraphthalate (C10H8O4). The gamma ray photons were detected by NaI(Tl) detector with resolution of 8.2 % at 662 keV, using radioactive gamma ray sources 57Co, 133Ba, 137Cs, 54Mn, 60Co, and 22Na at energies 122, 356, 511, 662, 840, 1170, 1275, and 1330 keV. Values of μ/ρ for the chosen polymers decrease with increasing energy. The results of investigated data are useful in plastic industry, building materials, agriculture fields radiation shielding, accelerator centers, polymer industry, medical field, etc.